INTEGRASI KEARIFAN LOKAL PERDIKAN CAHYANA DALAM BAHAN AJAR CERITA FIKSI UNTUK SISWA KELAS V SEKOLAH DASAR - Rani Darojah; Retno Winarni; Tri Murwaningsih (Fakultas Bahasa dan Seni UNP, 2019)
Abstract: The value of local wisdom “Perdikan Cahyana” which became the philosophy and principles of life in society would be more meaningful if it was manifested in learning. As a form of local wisdom manifestation in learning of Indonesian and Literature subject, especially fiction material is to develop instructional material which was meaningful and relevant to the environment and local wisdom values of the students. This research used research and development (R&D) method to develop instructional material of fiction story that was suitable with the students’ cultural needs, contexts, and then it was validated based on the criteria of the eligibility of instructional material. The local wisdom integration in the instructional material did not damage the material content, but it could strenghten the material. The development of this instructional material based on the local wisdom of “Perdikan Cahyana” which was aimed to achieve the learning objectives and also to converse and internalize the values of local wisdom had meet the instructional material feasibility based on the elibility criteria of the contents, language and readability, materials presentation, and graphics.Keywords: fiction material, perdikan cahyana, local culture.